The Effect Of Radec Model On Student Learning Motivation On Deliberation Materials In Grade 2 Elementary School - Fauziah, Delia Nurul (Current Issues on Elementary Education Journal, 2025)
This study aims to analyze the effect of RADEC (Read, Answer, Discuss, Explain, Create) Model in increasing students' learning motivation on the topic of deliberation in second grade elementary school students. The RADEC model was chosen because it can increase students' activeness in learning, especially on topics that involve group discussions, such as deliberation. The research method used in this study is quasi experimental design with non-equivalent control group design, where students who follow RADEC-based learning are placed in the experimental group, while the control group gets learning using the Flipped Classroom model. The instrument used to measure students' learning motivation is a questionnaire consisting of 10 items to assess the level of motivation. The results showed that students who took part in learning with the RADEC Model had very high learning motivation, with a percentage reaching 91.30%. This shows that the application of the RADEC Model can significantly increase students' learning motivation in deliberation lessons. Therefore, it can be concluded that the RADEC Model plays an effective role in increasing student learning motivation, especially in group discussion-based learning such as deliberation.